Analysis of high plasticity clayey soil improvement at subgrade level through Portland cement added to decrease volumetric change - Castro, M. (2020)
This research includes the potential for resistance and the expansion that the soil presents, this evaluation was carried out through CBR tests. The soil cement technique was used to improve the physical and mechanical characteristics; this process consists in mixing the material with Portland cement type I. That combination forms soil cement 10%, 15% y 20%, which present an increase of the CBR (max: 138.7% and min: 91.9%) achieving a type of extraordinary subgrade to resist the structure of the pavement and a reduction of 7.18% in the expansion of the samples.